2023
DOI: 10.1371/journal.pone.0291804
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17, C-reactive protein, Neutrophil-to-Lymphocyte ratio, Lymphocyte-to-Monocyte ratio, and lipid profiles in healthy menopausal women with or without hot flashes: A cross-sectional study

Nazila Didevar,
Parvaneh Rezasoltani,
Arash Pourgholaminejad
et al.

Abstract: Introduction The reciprocation between systemic inflammatory markers (SIMs), dyslipidemia, and hot flashes (HFs) can play a part in the pathogenesis of endothelial dysfunction through menopause. This study intended to determine the association between some SIMs, lipids, and HFs in healthy menopausal women. Materials and methods We designed a cross-sectional study in which 160 healthy menopausal women aged 40–60 were enrolled. Concerning their HFs status, they were stratified into two groups by consecutive sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…A study reported that menopausal women had higher concentrations of cytokines such as tumor necrosis factor (TNF)-alpha, interleukin (IL)-6, and CRP [14]. High levels of CRP in the blood can indicate systemic inflammation or inflammation in the body [15]. This inflammation can affect various body systems, including the genitourinary system, which includes the genital organs and urinary tract [16].…”
Section: Discussionmentioning
confidence: 99%
“…A study reported that menopausal women had higher concentrations of cytokines such as tumor necrosis factor (TNF)-alpha, interleukin (IL)-6, and CRP [14]. High levels of CRP in the blood can indicate systemic inflammation or inflammation in the body [15]. This inflammation can affect various body systems, including the genitourinary system, which includes the genital organs and urinary tract [16].…”
Section: Discussionmentioning
confidence: 99%